O entre-fronteiras decadentista de Drácula e O retrato de Dorian Gray - (:unkn) unknown (Universidade Federal de Goiás, 2017)
This research entitled: “The decadentist crossborders of Dracula and The Picture of Dorian Gray” presents an analysis on the intrinsic relationship between Bram Stoker’s Dracula (1897), and Oscar Wilde’s The Picture of Dorian Gray (1891), aiming at showing how the novel Dracula, considered an example of Victorian Gothic Literature, can be read as a representative of English Decadentism due to the dialogue established with The Picture of Dorian Gray. This dialogue can be seen through the acceptance of the faustic pact, an action that promotes situations similar to the ones created by the artificial experimentations engendered by Decadentism, since that decadent beings act attracted by sadistic and diabolic incursions (LEVIN, 1996, p.36). Thus, the intensification of the cult to the body as a mechanism to the fulfillment of art and pleasure in the universe of sensations promotes the corporeal learning of absolute knowledge as it happened to Faust. The artificialization of the decadent and vampiric body in search of sensations is fulfilled by the corporeal fluids: blood and sêmen. Liquids that possess useful functions in society. However, these valuable elements in decadent hands become instruments of joy. Thus, blood and sêmen can be propagator of life and death. Therefore they are fluids that become instruments to the joy of the monster, promoting in this way, the discovery of a new artificial universe of experiences. Thus, this research aims at proving through the decadent aesthetics, the reminiscences of the aesthete Dorian Gray in Stokers’s vampire, a supernatural vampire that artificializes his/her body, transforming it in a locus of art and pleasure.
The decadentist crossborders of Dracula and The Picture of Dorian Gray”
Keywords: Literatura inglesa; Decadentismo; Pacto fáustico; English literature; Decadentism; Faustic pact; LINGUISTICA, LETRAS E ARTES